Strategi Energi Vladimir Putin Dalam Mempertahankan Dominasi Rusia Di Negara-Negara Baltik - Chikitta Carnelian; Daru Purnomo; Adrianus Bintang Hanto Nugroho (Universitas Kristen Satya Wacana, 2017)
The EU Enlargement is a European Union (EU) effort to expand its territory over the entire European continent, including to Eastern Europe which is still under Russian influence. Russia is trying to take control again to the Baltic States which are the only post-Soviet countries to join the EU. Baltic membership in the EU and NATO leads to the direct attachment of the EU-Russia border that threatens the security of the Russian territory and other Russian national interests. Utilizing the development of its natural gas energy industry, Russia sought to restore its influence in the Baltic using a gas-based grand strategy as both natural resources and economic means. The EU's energy rivalry with Russia is regulated in Russia's energy policy implemented by Gazprom on the orders of the Kremlin which is under the control of Putin and his siloviki. The author uses Foreign Policy Analysis theory to analyze the suitability of Putin's energy policy and its bureaucracy with their grand strategy to see the possibility of achieving Russia's national goals to maintain influence in the Baltic states, protecting regional security and maintaining a balance of power in Europe.